American Canine Hepatozoonosis Causes Multifocal Periosteal Proliferation on CT: A Case Report of 4 Dogs - Coy, Cambridge L.; Evans, Jeremy B.; Lee, Alison M.; Dugat, Danielle R.; Levine, Jonathan M.; Griffin, John F. (Frontiers in Veterinary Science, 2022)
American canine hepatozoonosis (ACH) represents an important but relatively uncommon differential diagnosis in a dog with fever, muscle wasting, profound leukocytosis, and/or musculoskeletal pain. Despite this, obtaining a definitive diagnosis can prove difficult. Peripheral blood smears and whole-blood polymerase chain reaction (PCR) rely on rare parasitemia, and the gold standard diagnostic test (skeletal muscle biopsy) is uncommonly pursued due to its invasive and costly nature. Demonstration of characteristic periosteal proliferative lesions aids diagnosis. The lesions typically involve the more proximal long bones of the appendicular skeleton. The periosteal proliferation is of currently unknown pathogenesis, but its distribution is characteristic of this disease with few differential diagnoses. This case series describes the findings on computed tomography (CT) in 4 dogs with PCR- or cytologically-confirmed Hepatozoon americanum. All dogs had multifocal, bilaterally asymmetric, irregularly marginated, non-destructive, non-articular, periosteal proliferative lesions. Recognition of this unusual CT finding and awareness of this disease could assist in the diagnosis and subsequent treatment of dogs with ACH and may offer an additional indication for CT in cases of fever, muscle wasting, and myalgia.